PEMANFAATAN NILAI PEDULI SOSIAL CERITA RAKYAT DI KABUPATEN PURBALINGGA SEBAGAI PENGEMBANGAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BAHASA INDONESIA - Amalia, Wiwit Puji; Sumarwati, Sumarwati; Setiawan, Budhi (Universitas Sebelas Maret, 2018)
This research is a qualitative descriptive research aims to (1) describe and explain the structure of folklore of Purbalingga District, (2) to describe and explain the social care values contained in Purbalingga District folklore, (3) describe and explain the relevance of folklore as the character buildingand teaching material in Junior High School. Data and information are collected through informants and documents. Data collection is done through observation, recording, interview, and document analysis. Research sample is determined by purposive sampling technique. Validation of data is done by triangulation. The results of this research are:(1) the structure of folklore Purbalingga District, (2) social caring values contained in Purbalingga District folklore, (3) relevance of folklore as the character building and teaching material in Junior High School.